Effects of Fluorinated Carbonate Solvent Blends on High Voltage Parasitic Reactions in Lithium Ion Cells Using OCV Isothermal Microcalorimetry. Issue 10 (1st January 2016) - Glazier, S. L.; Downie, L. E.; Xia, J.; Louli, A. J.; Dahn, J. R.
Abstract : Fluorinated carbonates such as fluoroethylene carbonate (FEC) and di-2, 2, 2-trifluoroethyl carbonate (TFEC) improve cycling performance and decrease parasitic reactions at high potentials. However they also decrease cell life at lower voltage ranges compared to typical organic carbonate solvents. A method of quantifying the parasitic heat flow during open circuit and voltage hold conditions was implemented using isothermal microcalorimetry on Li-ion pouch cells to investigate the effect of additives in FEC:TFEC (3:7) and the effects of blending ethylene carbonate (EC):ethylmethyl carbonate (EMC) 3:7 with FEC:TFEC (3:7) in order to reduce parasitic reactions during operation at 4.2 V, 4.4 V and 4.6 V. Additives were found to lower parasitic heat flow in FEC:TFEC at all operating potentials, however to less of an effect at 4.6 V. Blending EC:EMC and FEC:TFEC resulted in decreased rates of parasitic reactions at all operating potentials compared to EC:EMC alone. Cells with unblended FEC:TFEC exhibited the lowest parasitic heat flow at 4.4 V and 4.6 V, although they produced more gas than EC:EMC containing blends. This work demonstrates the advantage of blending fluorinated carbonates with traditional solvents, particularly during use at low operating potentials, as well as demonstrating some advantages of fluorinated carbonates for high voltage lithium ion battery applications.